2018
DOI: 10.30731/ijcps.7.1.2018.38-47
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Spin and Pseudospin Solutions to the Dirac Equation for the Manning-Rosen Plus Eckart Potential and Yukawa-Like Tensor Interaction

Abstract: We solve the Dirac equation for the Manning-Rosen plus Eckart potential including a Coulomb-like tensor potential with arbitrary spin-orbit coupling quantum number κ. In the framework of the spin and pseudospin (pspin) symmetry, we obtain the energy eigenvalue equation and the corresponding eigenfunctions in closed form by using the Nikiforov-Uvarov method. Also special cases of the potential have been considered and their energy eigen values as well as their corresponding eigen functions have been obtained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…The same problem for ℓ = 0 have been studied in Ref. [49,50] as well, but our outcome disagrees with the result therein. We arrange this paper as follows: In Sec.…”
Section: Introductioncontrasting
confidence: 87%
“…The same problem for ℓ = 0 have been studied in Ref. [49,50] as well, but our outcome disagrees with the result therein. We arrange this paper as follows: In Sec.…”
Section: Introductioncontrasting
confidence: 87%
“…suggested that the strength of the angular momentum ( + 1) should be treated as an adjustable parameter K, not as a fixed quantity. Langer pointed out that K should be replaced with the term ( + regularizes the radial WKB wave function at the origin and ensure correct asymptotic behaviour at large quantum numbers [9][10][11][12][13][14][15][16][17] .…”
Section: (1)mentioning
confidence: 99%